Echo of its time : the history of the Federal District Court of Nebraska, 1867-1933 - Wunder, John R.; Scherer, Mark R. (University of Nebraska Press, 2019)
"Throughout its existencethe Federal District Court of Nebraska has echoed the dynamics of its time, reflecting the concerns, interests, and passions of the people who have made this statetheir home. Echo of Its Time explores the court's development, from its inception in 1867 through 1933, tracing the careers of its first four judges:Elmer Dundy, William Munger, Thomas Munger (no relation), and Joseph Woodrough, whose rulings addressed an array of issues and controversies echoing macro-level developments within the state, nation, and world. Echo of Its Time both informs and entertains while using the court's operations as a unique and accessible prism through which to explore broader themes in the history of the state and the nation. The book explores the inner workings of the court through Thomas Munger's personal correspondence, as well as the court's origins and growing influence under the direction of its legendary first judge, Elmer Dundy. Dundy handled many notable and controversial matters and made significant decisions in the field of Native American law, including Standing Bear v. Crook and Elk v. Wilkins. From the turn of the century through 1933, the court's docket reflected the dramatic and rapid changes in state, regional, and national dynamics, including labor disputes and violence, political corruption and Progressive Era reform efforts, conflicts between cattle ranchers and homesteaders, wartime sedition and "slacker" prosecutions, criminal enterprises, and the endless battles between government agents and bootleggers during Prohibition"--